2016
DOI: 10.1016/j.jjcc.2015.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Aortic dimensions by multi-detector computed tomography vs. echocardiography

Abstract: There is considerable variability between MDCT and ECHO measurements of the ascending aorta. Measuring the aortic diameter by the MIX provides the closest measurements and is advised for long-term follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…By contrast, use of the I-I convention in enddiastole on TTE significantly underestimated the dimensions obtained with CT and MRI. These results were confirmed by other authors [15,18]. Most studies comparing the various methods used to assess aortic dimensions with 2D TTE in healthy individuals showed that the L-L convention yielded larger dimensions than the I-I convention [6][7][8]11].…”
Section: Discussionsupporting
confidence: 82%
“…By contrast, use of the I-I convention in enddiastole on TTE significantly underestimated the dimensions obtained with CT and MRI. These results were confirmed by other authors [15,18]. Most studies comparing the various methods used to assess aortic dimensions with 2D TTE in healthy individuals showed that the L-L convention yielded larger dimensions than the I-I convention [6][7][8]11].…”
Section: Discussionsupporting
confidence: 82%
“…Both CMR and CCT, also, allow comprehensive assessment of entire aorta for quantifying aortic dilation or the presence of coarctation in patients with bicuspid aortic valve. 31 CCT is the preferred imaging modality to assess maximum diameter in patients with dilated aorta and also for sizing the aorta before surgery, while CMR can be used for serial evaluation to limit radiation. 32…”
Section: Aetiology and Mechanisms Of Armentioning
confidence: 99%
“…Most studies comparing 2-dimensional TTE with CT and MRI found that TTE significantly underestimates aortic root diameters compared with CT [162][163][164] and MRI, [163][164][165][166] likely related to off-axis image acquisition and root asymmetry. On the other hand, 3D TTE correlates well with CT. 165 Several studies also have demonstrated that abdominal ultrasound systematically underestimates the size of abdominal aortic aneurysms by ≈1 to 3 mm compared with CT. [167][168][169][170][171] In the nondissected thoracic and abdominal aorta, the agreement between diameter measurements obtained with CTA and MRA is good when the same analysis technique is used, [168][169][170][171] and interobserver agreement is excellent.…”
Section: Differences Within and Between Imaging Modalitiesmentioning
confidence: 99%